The Implementation of Progressivism Philosophy Based on Educational Entities in Indonesia - Efri Syamsul Bahri; Abdullah Mubarok (Sultan Publisher, 2024)
In order to improve the quality of human resources, education entities in Indonesia implement an education system that includes elementary, middle, and high levels. One philosophical approach widely used in educational entities in Indonesia is the progressivism philosophical model. This research aims to determine the implementation of the progressivism philosophy in education in Indonesia. This research uses qualitative methods with two approaches: descriptive and literature study. Data is obtained randomly from various database sources—data disbursement using keywords related to the research theme. Next, data analysis was carried out descriptively by grouping it based on educational entities. The results of this research show that the philosophy of progressivism has been applied to various educational entities in Indonesia: Early Childhood Education (PAUD), Elementary Schools, Government, Formal Education Institutions, Madrasas, and Islamic Community Organizations. The results of this research have contributed to the insight that future research needs to be carried out regarding applying the philosophy of progressivism to non-formal education entities. Entities that wish to apply the philosophy of progressivism to their entities must pay attention to the implementation carried out by various entities in Indonesia.